Biomoléculas orgánicas: Proteínas - Idrogo Medina, Alfonso (2018)
Education defined the process of preserving culture in addition to enriching that can be informal or formal. This is the last one that is fixed by a series of standards that a community wants its learners to reach. In that sense, Peruvian education has seen the need to standardize the learning of science through the area of science, technology and environment. This seeks to achieve an alphabetically scientific and research culture with a respect for nature and the surrounding environment but with a critical and innovative creative approach to save the problem that underlies day to day and thus contribute to improving the quality of life _x000D_ Consequently, it is necessary to present this work whose purpose is to achieve in high school students knowledge about proteins and their importance in biological life. That way students will understand that the consumption of this in the daily diet is important to not suffer diseases in the future